Optimalisasi Pojok Baca Sebagai Sarana Literasi Anak Di Desa Ngerangan - Khailla Utami; Famara Azka Aisyah; Imelda Wigati; Syifa Nur Addina (CV. ITTC INDONESIA, 2026)
Literacy is essential for helping children understand information and build learning habits, yet accessible reading facilities remain needed at the community level. Ngerangan Village, Bayat District, Klaten Regency, has a reading corner whose potential remained underutilized due to limited book collections and poor spatial arrangement. This community service activity aimed to optimize the reading corner through room renovation, collection development, and its use for tutoring activities, targeting 13 children aged 7–13. The program included socialization, room renovation, book donation drives, and book organization, followed by routine tutoring and a closing competition used to collect satisfaction data. Descriptive quantitative analysis showed an overall satisfaction level of 96.5%, categorized as very satisfied, with facility condition rated highest (98.6%) and collection completeness needing further improvement (92.8%). These results confirm that reading corner revitalization effectively supports community literacy, provided book collections continue to be expanded.